2012
DOI: 10.1111/j.1654-1103.2012.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the variation of woody plant β‐diversity in a landscape of secondary tropical dry forests across spatial scales

Abstract: Question What is the relative importance of forest successional age, environmental heterogeneity, landscape structure and spatial structure of sampling sites on β‐diversity of tropical dry forests (TDF)? How do the magnitude of β‐diversity and the relative influence of factors, processes and mechanisms driving β‐diversity differ at different spatial grains? What are the effects of stand age on β‐diversity? Location Yucatán Peninsula, México. Methods Floristic composition was obtained from a hierarchical survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 81 publications
(171 reference statements)
3
26
0
2
Order By: Relevance
“…López-Martínez et al (2013) observed significant values for environmental variables and spatial structure, and they interpreted these results as a proxy for both niche partitioning (environment variables) and dispersal limitation (spatial structure), despite the limitations of the approach (Diniz-Filho et al 2012). Based on our findings, spatial effects may be due to topographical variations in the region, as they generate high spatial variability in environmental variables and could serve as physical or climatic barriers to species dispersal.…”
Section: Discussionmentioning
confidence: 50%
“…López-Martínez et al (2013) observed significant values for environmental variables and spatial structure, and they interpreted these results as a proxy for both niche partitioning (environment variables) and dispersal limitation (spatial structure), despite the limitations of the approach (Diniz-Filho et al 2012). Based on our findings, spatial effects may be due to topographical variations in the region, as they generate high spatial variability in environmental variables and could serve as physical or climatic barriers to species dispersal.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, stand age explained less than 10% of variation in species composition of zoochorous and autochorous species, and 20% of the anemochorous β-diversity. In this same study area, [14] found that stand age explained only 3% of the total variation in species composition of all woody species. These contrasting results clearly illustrate the importance of considering different functional groups when evaluating the ecological factors that influence β-diversity.…”
Section: Discussionmentioning
confidence: 76%
“…This may be partly attributed to their relatively short stature, which may impose critical limits on their dispersal capacity, resulting in a strong spatial autocorrelation in species composition. Using the same data set and (local) spatial grain of this study, [14] found that both environmental variables and the spatial structure of sampling sites had similar influences on overall β-diversity of woody species. Our results clearly show that this general pattern masks major differences in the relative importance of environmental filters vs. dispersal limitation among growth forms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In other words, the inclusion of different habitat conditions at a larger scale (cluster of four plots over an area of 1.0 ha) may reveal a relationship between species richness and habitat heterogeneity that is not captured at the local, single-plot scale [56]. For example, the variety of land cover classes within clusters of four plots may be correlated with species richness, reflecting different topographic conditions and stages of forest succession, as also found by [27,57], respectively. Both studies were performed in tropical dry forests of the Yucatan Peninsula.…”
Section: Effects Of Plot Size and Plot Design On Species Richness Andmentioning
confidence: 86%